2003
DOI: 10.1021/ol030123z
|View full text |Cite
|
Sign up to set email alerts
|

Aryloxy Radicals from Diaryloxydiazirines:  α-Cleavage of Diaryloxycarbenes or Excited Diazirines?

Abstract: The synthesis of diaryloxydiazirines, precursors to diaryloxycarbenes, is described. Thermolyses of the diazirines afford anticipated carbene products, but photolyses afford both carbenes and aryloxy radicals by alpha-scission. UV spectra of the carbenes and radicals are observed. [reaction: see text]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…The formation of radical products ArCH 3 (Table ) requires photolysis of the diazirines, and we suggest that the diazirines' excited states ( 4* ) are the key intermediates. Recently, we reported that photolyses of diaryloxydiazirines 9 produced aryloxy radicals 10 via α-scission of the diazirines' excited states 9* ; thermolyses of 9 , however, gave only products expected from diaryloxycarbenes 11 (dimers, O−H insertion products) . We suggest that a related scenario accounts for the present findings; cf.…”
supporting
confidence: 62%
“…The formation of radical products ArCH 3 (Table ) requires photolysis of the diazirines, and we suggest that the diazirines' excited states ( 4* ) are the key intermediates. Recently, we reported that photolyses of diaryloxydiazirines 9 produced aryloxy radicals 10 via α-scission of the diazirines' excited states 9* ; thermolyses of 9 , however, gave only products expected from diaryloxycarbenes 11 (dimers, O−H insertion products) . We suggest that a related scenario accounts for the present findings; cf.…”
supporting
confidence: 62%
“…N -Methanesulfonyloxy- O -phenylisourea ( 7 ) was oxidized to phenoxychlorodiazirine ( 8 ) by NaOCl in methanol. The diazirine, purified by flash chromatography, was obtained in 84% yield .…”
mentioning
confidence: 99%
“…1 H and 13 C NMR of 16 were in very good agreement with literature values. 23 16 was further characterized by ES MS, including exact mass determination. Although 16 has been reported in the literature earlier, 23 the single crystal X-ray structure has not been reported previously and is therefore attached as supplementary material.…”
Section: Methodsmentioning
confidence: 99%